2019
DOI: 10.1016/j.jmbbm.2019.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of gap size on the development of fracture union with a micro external fixator

Abstract: Increasingly, the rat femoral fracture model is being used for preclinical investigations of fracture healing, however, the effect of gap size and its influence on mechanobiology is not well understood. We aimed to evaluate the influence of osteotomy gap on osteotomy healing between the previously published extremes of guaranteed union (0.5 mm) and non-union (3 mm) using this model.A femoral osteotomy in 12–14 week old female Wistar rats was stabilised with a micro fixator (titanium blocks, carbon fiber bars) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
2
25
0
Order By: Relevance
“…Previous anatomical studies have shown that the distance of the uncovertebral joint is about 2 mm, which is much shorter than the central height (about 5 to 8 mm) of the intervertebral space in the cervical spine [31]. This may have similar mechanism with fracture healing, which is influenced by the gap size [32]. Second, special biomechanical environment.…”
Section: Discussionmentioning
confidence: 99%
“…Previous anatomical studies have shown that the distance of the uncovertebral joint is about 2 mm, which is much shorter than the central height (about 5 to 8 mm) of the intervertebral space in the cervical spine [31]. This may have similar mechanism with fracture healing, which is influenced by the gap size [32]. Second, special biomechanical environment.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 48 female Wistar rats, weighing 203 g to 232 g and aged between six and nine months, underwent gaseous anaesthesia. Using anatomical landmarks and a custom precision jig-guide system, 22 four bicortical threaded 1.4 mm stainless steel fixator pins were placed in the craniomedial femur. Pins exited through separate stab incisions and the custom variable spacing fixator was attached.…”
Section: Methodsmentioning
confidence: 99%
“…In order to analyze the callus in each slice included in the ROI, a shrink wrap protocol was used to stretch over holes < 40 pixels. 22 …”
Section: Methodsmentioning
confidence: 99%
“…We hypothesise that this unconstrained configuration, in which the line of force acting on the femoral neck will not necessarily be para-axial, may thus be more physiologically representative of femoral neck properties. 19…”
Section: Introductionmentioning
confidence: 99%